Pengaruh Kepemimpinan, Reward, dan Punishment Terhadap Kinerja Karyawan pada Auto 2000 By Pass Padang - Dennis Salsa Tiara (Pusat Riset dan Inovasi Nasional, 2023)
In order to investigate the effects of transformational leadership and self-efficacy on employee performance in Auto 2000 By Pass Padang, job satisfaction will be used as an intermediary variable. All 50 employees of Auto 2000 By Pass Padang received questionnaires as part of the data collection process. The analytical method used in this study was structural equation modeling (SEM) with partial least squares (PLS). The study's findings are as follows: (1) Leadership has a small but positive impact on employee performance. (2) Reward has a favorable and significant impact on employee performance. (3) Punishment has a significant and favorable impact on an employee's performance.